VD_FINDINFO Jug / 2015 / 348 vom 13. Mai 2015 - VD Tribunal cantonal (2015)
MAÎTRISE DU VÉHICULE, LOI FÉDÉRALE SUR LA CIRCULATION ROUTIÈRE, INTENTION | 31 LCR, 398 al. 4 CPP (CH), 406 al. 1 let. c CPP (CH), 14 al. 3 LVCPP